2021
DOI: 10.1177/02692163211034120
|View full text |Cite
|
Sign up to set email alerts
|

Bereaved relatives’ quality of life before and during the COVID-19 pandemic: Results of the prospective, multicenter, observational eQuiPe study

Abstract: Background: The death of a loved one is considered as one of the most stressful life events. During the COVID-19 pandemic, grief processes are potentially affected by measures such as social distancing and self-quarantine. Aim: The aim of this study was to give insight in the impact of the COVID-19 pandemic on quality of life, social support, and self-care of bereaved relatives of people with advanced cancer in order to evaluate whether care for bereaved relatives during the COVID-19 pandemic should be improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
(39 reference statements)
0
8
0
1
Order By: Relevance
“…Death of relatives decreased the mean score of all domains, yet, only the physical and environmental domains were significantly affected in this study. To the contrary, Ham et al ( 48 ), found that the COVID-19 pandemic had no substantial influence on the wellbeing of grieving families in the short term. We speculate that the effect was not apparent as the sample size was relatively small ( n = 91), which may not be representative of the population.…”
Section: Discussionmentioning
confidence: 97%
“…Death of relatives decreased the mean score of all domains, yet, only the physical and environmental domains were significantly affected in this study. To the contrary, Ham et al ( 48 ), found that the COVID-19 pandemic had no substantial influence on the wellbeing of grieving families in the short term. We speculate that the effect was not apparent as the sample size was relatively small ( n = 91), which may not be representative of the population.…”
Section: Discussionmentioning
confidence: 97%
“…This is crucial given discrepancies in emerging evidence. 41 43 The experiences of bereaved men and people from Black and minority ethnic communities during the pandemic require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is needed to examine the impact of end-of-life care experiences and pandemic-related social challenges on bereavement outcomes, and to determine the prevalence of poor bereavement outcomes including prolonged grief disorder among people bereaved during the pandemic, with comparisons to non-pandemic times. This is especially crucial given some discrepancies in emerging evidence [39][40][41] . The experiences of bereaved men and people from black and minority ethnic communities during the pandemic require further research.…”
Section: Discussionmentioning
confidence: 99%